ChemInform Abstract: Efficient Syntheses of 2‐Fluoroalkylbenzimidazoles and ‐benzothiazoles. Issue 16 (28th March 2013) - Rene, Olivier; Souverneva, Alexandra; Magnuson, Steven R.; Fauber, Benjamin P.
Abstract A facile synthesis of the title compounds is achieved by condensation of fluorinated carboxylic acids and aromatic diamines or aminothiophenols.